“Gestión del talento humano y su incidencia en el desempeño laboral de la empresa Terratecnica S.A.” - Bustamante Coello, Angy Mayli (2025)
This study aims to analyze human talent management and its impact on job performance at TERRATECNICA SA, a company located in the Valencia Canton of Los Ríos Province. It seeks to identify weaknesses in current practices and propose strategies grounded in theory and evidence to improve employee productivity, motivation, and development. Among the problems identified at the company are high staff turnover, lack of motivation, and poor working conditions that can affect employee well-being. The theoretical framework addresses key concepts such as job competencies, job performance, and successful management models. The methodology uses a mixed approach, combining descriptive and exploratory techniques with data collection through surveys, interviews, and direct observation. The results analyze the impact of human talent management on business performance, considering both internal and external factors affecting the organization. The conclusions and recommendations focus on strengthening human talent management practices at TERRATECNICA SA through organizational policies, training, and motivational strategies, which lead to improved personnel management within the company and promote sustainable and efficient organizational development.